Sericin coats of silk fibres, a degumming waste or future material? - Yunong Yuan; Mohammad Nasri; Azadeh Manayi; Junying Zhang; Chunyong Wu; Tae-Joon Jeon; Lifeng Kang (Materials Today Bio)
Silk is a fibrous biopolymer with a recorded history in the textile industries for centuries. This fibre is constituted of two different proteins: fibroin and sericin, of which the latter accounting for approximately 20–30 % of the silk mass. Silk sericin (SSER) was previously considered as a waste by-product in silk fibroin extraction. SSER has recently garnered significant scientific interest due to its extensive biological and pharmacological properties. These include antioxidant effects, biocompatibility, low immunogenicity, controlled biodegradability, and the ability to induce cell proliferation. This review covers studies about various aspects of this emerging material, namely, its general morphology, specific structure, molecular weight, features of different layers, and gene sequences. The impact of different extraction methods and the application of extracted SSER based on molecular weight are discussed. Additionally, the characteristic functional groups in the amino acids of sericin facilitate its applications in regenerative medicine, wound healing, drug delivery, textile, environment, and energy, in various forms like hydrogels, films, scaffolds, and conduits. SSER-based materials offer great potentials for multi-functional applications in the upcoming decades, showcasing adaptability for various functional uses and promising future technological advancements.